Pilot-scale evaluation of native plant–based constructed wetland performance in a cold climate - Adrian L. D. Paul; Alexandre Licinio; Marie-Christine Simard; Roberta D’Camp; Michel Labrecque (Environmental Science and Pollution Research, 2026)

Biodiversity of coastal epibenthic macrofauna in Eastern Canadian Arctic: Baseline mapping for management and conservation - Bruno L. Gianasi; Christopher W. McKindsey; Philippe Archambault; Nathalie Simard; Kimberly L. Howland (Frontiers in Marine Science, 2022)
Arctic ecosystems are changing rapidly due to global warming, industrial development, and economic growth. However, the ecological consequences for these ecosystems are difficult to predict due to limited knowledge on species abundance, distribution, and biodiversity patterns. This study evaluated the diversity and assemblage composition of epibenthic macrofauna in shallow coastal areas from five Eastern Arctic locations with increasing economic and shipping activity. Benthic trawls (n=198) were conducted in nearshore coastal habitats of Anaktalak Bay (Labrador), Churchill (Manitoba), Deception Bay (Quebec), Iqaluit (Nunavut), and Milne Inlet (Nunavut), at depths between 3 and 30 m. Diversity and assemblage composition were compared at various taxonomic levels from phylum to species and correlations with broad oceanographic variables were investigated to identify potential drivers of biodiversity. The spatial variability of benthic assemblages was also assessed within each study location. A total of 297,417 macroinvertebrates was identified, belonging to 900 taxa. Abundance and taxonomic richness were highest in Anaktalak Bay. Shannon-Wiener diversity was higher in Anaktalak Bay, Iqaluit, and Milne Inlet than in Churchill and Deception Bay. Churchill showed the lowest diversity metrics among locations. No relationships were observed between diversity and depth, chlorophyll- a , particulate organic carbon, sea surface temperature, or sea ice duration. Assemblages differed among locations at all taxonomic levels, with the highest dissimilarities at the species level; however, dispersion of samples within-groups was significant, suggesting that factors other than locations (e.g., habitat type) influence assemblage composition. While Churchill, Deception Bay, and Iqaluit showed distinct local spatial patterns in diversity metrics and assemblage composition, no patterns were detected in Anaktalak Bay and Milne Inlet. This study represents one of the largest systematic assessments of coastal epibenthic biodiversity in the Canadian Arctic. It identifies patterns of biodiversity and assemblage composition and provides a baseline for studies of community change and the development of informed management and conservation strategies for Arctic coastal ecosystems.

Experimental Analysis of Survival and Recovery of Ship Fouling Mussels During Transit Between Marine and Freshwaters - Cyrena Riley; David Drolet; Jesica Goldsmit; Jaclyn M. Hill; Kimberly L. Howland; Marie-France Lavoie; Cynthia H. McKenzie; Nathalie Simard; Christopher W. McKindsey (Frontiers in Marine Science, 2022)
Ships and boats may transport whole communities of non-indigenous species (NIS) through hull biofouling, some members of which may become invasive. Several studies have evaluated the diversity of these communities, but very few have analyzed the survival of organisms after their voyages into different and potentially inhospitable conditions. This factor is important to consider because the last port of call approach for risk assessments assumes that if the conditions observed in the last port of call are different from those observed in a receiving port, risks are diminished or null. Using an innovative experimental system, we tested the survival and recovery of the marine blue mussel ( Mytilus edulis ) and the freshwater zebra mussel ( Dreissena polymorpha ) by exposing them to adverse salinity conditions at varying temperatures to simulate ships and boats transiting to ports or marinas with contrasting environmental conditions. Both mussel species, which are well-known for their adaptability to new environments as aquatic NIS, survived better at colder temperatures, with blue mussels surviving up to 14 days in freshwater, and zebra mussels up to 8 days in marine water. This highlights the importance of considering the resistance of fouling organisms to adverse conditions in vector and species risk assessments.

Water resource development and sturgeon (Acipenseridae): state of the science and research gaps related to fish passage, entrainment, impingement and behavioural guidance - S. J. Cooke; J. J. Cech; D. M. Glassman; J. Simard; S. Louttit; R. J. Lennox; L. Cruz-Font; C. M. O’Connor (Reviews in Fish Biology and Fisheries, 2020)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Application of the metabolic scaling theory and water–energy balance equation to model large‐scale patterns of maximum forest canopy height - Sungho Choi; Christopher P. Kempes; Taejin Park; Sangram Ganguly; Weile Wang; Liang Xu; Saikat Basu; Jennifer L. Dungan; Marc Simard; Sassan S. Saatchi; Shilong Piao; Xiliang Ni; et al. (Global Ecology and Biogeography, 2016)
Aim Forest height, an important biophysical property, underlies the distribution of carbon stocks across scales. Because in situ observations are labour intensive and thus impractical for large‐scale mapping and monitoring of forest heights, most previous studies adopted statistical approaches to help alleviate measured data discontinuity in space and time. Here, we document an improved modelling approach which links metabolic scaling theory and the water–energy balance equation with actual observations in order to produce large‐scale patterns of forest heights. Methods Our model, called allometric scaling and resource limitations (ASRL), accounts for the size‐dependent metabolism of trees whose maximum growth is constrained by local resource availability. Geospatial predictors used in the model are altitude and monthly precipitation, solar radiation, temperature, vapour pressure and wind speed. Disturbance history (i.e. stand age) is also incorporated to estimate contemporary forest heights. Results This study provides a baseline map ( c . 2005; 1‐km 2 grids) of forest heights over the contiguous United States. The Pacific Northwest/California is predicted as the most favourable region for hosting large trees ( c . 100 m) because of sufficient annual precipitation (> 1400 mm), moderate solar radiation ( c . 330 W m −2 ) and temperature ( c . 14 °C). Our results at sub‐regional level are generally in good and statistically significant ( P ‐value Main conclusions We improved the metabolic scaling theory to address variations in vertical forest structure due to ecoregion and plant functional type. A clear mechanistic understanding embedded within the model allowed synergistic combinations between actual observations and multiple geopredictors in forest height mapping. This approach shows potential for prognostic applications, unlike previous statistical approaches.

Multiple factors influence plant richness and diversity in the cold and dry boreal forest of southwest Yukon, Canada - Shyam K. Paudel; Patrick O. Waeber; Suzanne W. Simard; John L. Innes; Craig R. Nitschke (Plant Ecology, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Access to mycorrhizal networks and roots of trees: importance for seedling survival and resource transfer - François P. Teste; Suzanne W. Simard; Daniel M. Durall; Robert D. Guy; Melanie D. Jones; Amanda L. Schoonmaker (Ecology, 2009)
Mycorrhizal networks (MNs) are fungal hyphae that connect roots of at least two plants. It has been suggested that these networks are ecologically relevant because they may facilitate interplant resource transfer and improve regeneration dynamics. This study investigated the effects of MNs on seedling survival, growth and physiological responses, interplant resource (carbon and nitrogen) transfer, and ectomycorrhizal (EM) fungal colonization of seedlings by trees in dry interior Douglas‐fir ( Pseudotsuga menziesii var. glauca ) forests. On a large, recently harvested site that retained some older trees, we established 160 isolated plots containing pairs of older Douglas‐fir “donor” trees and either manually sown seed or planted Douglas‐fir “receiver” seedlings. Seed‐ and greenhouse‐grown seedlings were sown and planted into four mesh treatments that served to restrict MN access (i.e., planted into mesh bags with 0.5‐, 35‐, 250‐μm pores, or without mesh). Older trees were pulse labeled with carbon ( 13 CO 2 ) and nitrogen ( 15 NH 4 15 NO 3 ) to quantify resource transfer. After two years, seedlings grown from seed in the field had the greatest survival and received the greatest amounts of transferred carbon (0.0063% of donor photo‐assimilates) and nitrogen (0.0018%) where they were grown without mesh; however, planted seedlings were not affected by access to tree roots and hyphae. Size of “donor” trees was inversely related to the amount of carbon transferred to seedlings. The potential for MNs to form was high (based on high similarity of EM communities between hosts), and MN‐mediated colonization appeared only to be important for seedlings grown from seed in the field. These results demonstrate that MNs and mycorrhizal roots of trees may be ecologically important for natural regeneration in dry forests, but it is still uncertain whether resource transfer is an important mechanism underlying seedling establishment.

Genomic characterization of swine caliciviruses representing a new genus of Caliciviridae - Yvan L’Homme; Raphaël Sansregret; Étienne Plante-Fortier; Anne-Marie Lamontagne; Mourad Ouardani; Geneviève Lacroix; Carole Simard (Virus Genes, 2009)

Polymorphism of intron‐1 in the voltage‐gated sodium channel gene of Anopheles gambiae s.s. populations from Cameroon with emphasis on insecticide knockdown resistance mutations - JOSIANE ETANG; JOSE L. VICENTE; PHILIPPE NWANE; MOUHAMADOU CHOUAIBOU; ISABELLE MORLAIS; VIRGILIO E. DO ROSARIO; FREDERIC SIMARD; PARFAIT AWONO‐AMBENE; JEAN CLAUDE TOTO; JOAO PINTO (Molecular Ecology, 2009)
Sequence variation at the intron‐1 of the voltage‐gated sodium channel gene in Anopheles gambiae M‐ and S‐forms from Cameroon was assessed to explore the number of mutational events originating knockdown resistance ( kdr ) alleles. Mosquitoes were sampled between December 2005 and June 2006 from three geographical areas: (i) Magba in the western region; (ii) Loum, Tiko, Douala, Kribi, and Campo along the Atlantic coast; and (iii) Bertoua, in the eastern continental plateau. Both 1014S and 1014F kdr alleles were found in the S‐form with overall frequencies of 14% and 42% respectively. Only the 1014F allele was found in the M‐form at lower frequency (11%). Analysis of a 455 bp region of intron‐1 upstream the kdr locus revealed four independent mutation events originating kdr alleles, here named MS1 ‐1014F, S1‐1014S and S2‐1014S kdr‐ intron‐1 haplotypes in S‐form and MS3‐1014F kdr‐ intron‐1 haplotype in the M‐form. Furthermore, there was evidence for mutual introgression of kdr 1014F allele between the two molecular forms, MS1 and MS3 being widely shared by them. Although no M/S hybrid was observed in analysed samples, this wide distribution of haplotypes MS1 and MS3 suggests inter‐form hybridizing at significant level and emphasizes the rapid diffusion of the kdr alleles in Africa. The mosaic of genetic events found in Cameroon is representative of the situation in the West–Central African region and highlights the importance of evaluating the spatial and temporal evolution of kdr alleles for a better management of insecticide resistance.

Genetic diversity of porcine Norovirus and Sapovirus: Canada, 2005–2007 - Yvan L’Homme; Raphaël Sansregret; Étienne Plante-Fortier; Anne-Marie Lamontagne; Geneviève Lacroix; Mourad Ouardani; Jonathan Deschamps; Geneviève Simard; Carole Simard (Archives of Virology, 2009)

Tree proximity, soil pathways and common mycorrhizal networks: their influence on the utilization of redistributed water by understory seedlings - Amanda L. Schoonmaker; François P. Teste; Suzanne W. Simard; Robert D. Guy (Oecologia, 2007)

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

PCNA Up-Regulation in Cerebral Vessels with Angiotensin II-Hypertension: Abnormal Regulation of Ca2+ Channel and Nitrate Tolerance Associated with Alternative Splicing of cGKI - A. Ivanov; S. Ivanova; L. V. Melnitchenko; V. Gerzanich; M. F. Shuba; J. M. Simard (Neurophysiology, 2003)

SMN gene duplication and the emergence of the SMN2 gene occurred in distinct hominids: SMN2 is unique to Homo sapiens - C. Rochette; N. Gilbert; L. Simard (Human Genetics, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)